Venomous Freshwater Fish: Catfish and Freshwater Stingrays - Haddad, Vidal [UNESP] (2016)
The authors comment the actual research on the properties of the toxins of the freshwater venomous fish and their potential use in Human Medicine. They discuss the mechanisms of inoculation, biochemical characteristics of the venoms, and clinical/therapeutical aspects of the envenomations, with emphasis in their studies on freshwater stingrays and freshwater catfish, the fish most frequently associated with human injuries in these environments.